Conditions for blister formation during thermal cycles of Al–Si–Cu–Fe alloys for high pressure die-casting. (15th February 2016) - Ozhoga-Maslovskaja, Oksana; Gariboldi, Elisabetta; Lemke, Jannis Nicolas
Abstract: The mechanism of blister formation during thermal cycle in a High Pressure Die Cast Al–9Si–3Cu–Fe alloy (EN 46000) was investigated by means of FEM simulation of a pressurized subsurface defect, considering the high-temperature elastoplastic behavior experimentally derived. The effect of parameters related to initial defect geometry, location and maximum temperature was analyzed. Blister formation was considered to occur as the maximum surface displacement after a thermal cycle exceeded 0.005 mm. It was shown that, for a given reference gas pressure, pore volume and depth, as well as temperature, blisters were developed from pores below a critical aspect ratio, as a result of high plastic strain accumulation in localized regions laying between the pore and the outer surface (ligament). Similarly, critical ligament thickness was identified and correlated to temperature and reference gas pressure. The development of blisters at temperatures lower than 400 °C from pores with reference pressure 90 MPa was predicted for a wide range of aspect ratios and ligament thickness. The possible occurrence of blisters in conventional HPDC components during heat treatment cycles at 350 °C was modeled for different pore pressures in the case of surface-near defects, mainly from lamina-shaped pores and was experimentally confirmed. Graphical abstract: Highlights: Critical conditions for blister formation of Al–9Si–3Cu–Fe alloy are identified via a FE model. Blister formation is modeled for wide range of temperatures, pore pressure, shape, location, and size. Strain field shows blister formation related to strain localization, depending of pore geometry. Lamina-shaped discontinuities of cast part are most critical for blister formation.